1993
DOI: 10.1021/bi00078a012
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an anticoagulant protein homologous to botrocetin from the venom of Bothrops jararaca

Abstract: We previously isolated a unique anticoagulant protein named IX/X-bp (factor IX/factor X-binding protein) from the venom of the habu snake Trimeresurus flavoviridis. We recently determined its primary structure and found that this protein had a structure homologous to the carbohydrate-recognition domains of C-type lectins. Most interestingly, a high homology was found between this protein and botrocetin, an inducer of platelet agglutination found in the venom of the jararaca snake Bothrops jararaca. To examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…In addition to IX/ X-bp from the habu snake venom, proteins structurally related to the regulatory subunit of CA-1 are widely distributed in viper venoms. We have identified homologues of IX/X-bp in venoms of Bothrops jararaca (27) and Deinagkistrodon acutus (28). Moreover, numerous proteins with structures very similar to IX/X-bp but with totally different pharmacological actions have been found in venoms of various Viperidae snakes, and appear to constitute a unique protein family.…”
Section: Table IIImentioning
confidence: 99%
“…In addition to IX/ X-bp from the habu snake venom, proteins structurally related to the regulatory subunit of CA-1 are widely distributed in viper venoms. We have identified homologues of IX/X-bp in venoms of Bothrops jararaca (27) and Deinagkistrodon acutus (28). Moreover, numerous proteins with structures very similar to IX/X-bp but with totally different pharmacological actions have been found in venoms of various Viperidae snakes, and appear to constitute a unique protein family.…”
Section: Table IIImentioning
confidence: 99%
“…It has been found that the heterodimers isolated from different snake venoms normally possess different target proteins and therefore that these heterodimers can be grouped into four classes as follows: (i) factor X/IX binding proteins (Atoda & Morita, 1989;Atoda et al, 1995;Sekiya et al, 1993;Chen & Tsai, 1996), (ii) -thrombinbinding protein/inhibitors (Zingali et al, 1993;Castro et al, 1998), (iii) vWF-binding proteins (Andrews et al, 1989;Hamako et al, 1996), and (iv) platelet GP binding proteins (Peng et al, 1991;Taniuchi et al, 1995;Andrews et al, 1996;Kawasaki et al, 1996;Fujimura et al, 1995;Peng et al, 1993;Sakurai et al, 1998). For example, of the snake-venom C-type lectin-like proteins that possess the activity of inducing platelet aggregation, convulxin (Polgar et al, 1997;Jandrot-Perrus et al, 1997), 50 kDa alboaggregin (Andrews et al, 1996) and alboaggregin-A (Peng et al, 1992;Kowalska et al, 1998) are con®rmed to be GPIb-binding proteins, while botrocetin (Fujimura et al, 1991;Sugimoto et al, 1991) and bitiscetin (Hamako et al, 1996) have the potential to bind vWF.…”
Section: Resultsmentioning
confidence: 99%
“…Their structures are homologous to each other: a Gla domain is located at the N-terminus followed by two growth-factor domains, one activation peptide or connecting domain and one catalytic domain (Yoshitake et al, 1985;Leytus et al, 1986). A family of coagulation factor IX/X binding proteins (abbreviated IX/X-BPs) has been identi®ed in snake venoms and contains many peptides and proteins that affect haemostasis and thrombosis (Markland, 1998;Matsui et al, 2000;Andrews & Berndt, 2000;Atoda & Morita, 1989;Atoda et al, 1995Atoda et al, , 1998Sekiya et al, 1993;Chen & Tsai, 1996;Xu et al, 2000). Furthermore, this family belongs to a superfamily termed the snake-venom C-type lectin-like proteins.…”
Section: Introductionmentioning
confidence: 99%